The effect of combinations of a glyphosate-based herbicide with various clinically used antibiotics on phenotypic traits of Gram-negative species from the ESKAPEE group - Hanane Zerrouki; Aïcha Hamieh; Linda Hadjadj; Jean-Marc Rolain; Sophie Alexandra Baron (Scientific Reports, 2024)
Abstract The emission of glyphosate and antibiotic residues from human activities threatens the diversity and functioning of the microbial community. This study examines the impact of a glyphosate-based herbicide (GBH) and common antibiotics on Gram-negative bacteria within the ESKAPEE group (Enterococcus faecium, Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumannii, Pseudomonas aeruginosa, Enterobacter spp. and Escherichia coli). Ten strains, including type and multidrug-resistant strains for each species were analysed and eight antibiotics (cefotaxime, meropenem, aztreonam, ciprofloxacin, gentamicin, tigecycline, sulfamethoxazole-trimethoprim, and colistin) were combined with the GBH. While most combinations yielded additive or indifferent effects in 70 associations, antagonistic effects were observed with ciprofloxacin and gentamicin in five strains. GBH notably decreased the minimum inhibitory concentration of colistin in eight strains and displayed synergistic activity with meropenem against metallo-β-lactamase (MBL)-producing strains. Investigation into the effect of GBH properties on outer membrane permeability involved exposing strains to a combination of this GBH and vancomycin. Results indicated that GBH rendered strains sensitive to vancomycin, which is typically ineffective against Gram-negative bacteria. Furthermore, we examined the impact of GBH in combination with three carbapenem agents on 14 strains exhibiting varying carbapenem-resistance mechanisms to assess its effect on carbapenemase activity. The GBH efficiently inhibited MBL activity, demonstrating similar effects to EDTA (ethylenediaminetetraacetic acid). Chelating effect of GBH may have multifaceted impacts on bacterial cells, potentially by increasing outer membrane permeability and inactivating metalloenzyme activity.